Technical writing - Vicente, Corazon C.;Soria, Wenceslawa B.;Mogol, Ernani S.;Sumanga, Gloria R. ([Place of publication not identifed] : [publisher not identified], 1997)
This book consists of reprints, excerpts, adaptations, abstracts, or summaries of discussions from various technical books and periodicals as well as original material. Technical Writing, which is intended to play even a small role, though indirectly, in the realization of the educational objectives of the new Charter of the Philippines. Technical writing is indeed to provide one aspect of the technical students' training - the preparation of technical reports, letters, and articles, from the planning stage to the transmittal, mailing, or publication of the completed material.
1. An Overall View of Technical Writing -- 2. Basic Techniques of Technical Writing -- 3. Business Letters -- 4. Technical Reports -- 5. Technical Magazine Articles -- 6. Contemporary Communication.
Includes bibliographical references.
Keywords: TECHNICAL WRITING